دراسة تأثير أشعة غاما على تشتت قرينة الانكسار لأغشية رقيقة من البوليسيترين وفق نموذجي ويمبل - ديدمينكو وسيللماير - ختام قنجراوي (Tishreen University, 2018)
Two membranes of polysterene were prepared, pure and radiated with Gamma Rays, by casting method. The study  included recording the transmittance (T) spectrum in the range (400-900)nm, then calculating the values of the absorbance (A), the reflectance (R), the absorption coefficient ( 14خ±"> ), extinction coefficient (Ko), and refractive index (no) for the polysterene membranes before and after the irradiation. The effect of Gamma Rays on the refractive index dispersion by Wemple-Didomenico and Sellmeier models was studied. It was observed that ɣ Rays radiation lead to an increase in the transmittance (T) and a decrease reflectance (R) and absorbance (A), also a decrease in the refractive index values (no). Some special parameters in the Wemple-Didomenico model were calculated, like The Single Oscillator Energy (Eo), and Dispersion Energy (Ed) according to the refractive index (no). In Addition Some special parameters in the Sellmeier model were calculated, like Average Oscillator Wavelength (λo)nm, and Average Oscillator Length (So). According to Wemple-Didomennco model the values of the refractive index dispersion is closer to (1.85) in the pure sample but decreases in the radiated sample to (1.0826) for the low energies. According to Sellmeier it draws near to  (1.83) in the pure sample while it decreases to (1.14) for irradiated sample at the long waves. تم تحضير غشاءين من البوليستيرين PS( Polysterene ) نقي ومشعع بأشعة غاما ( Gamma Rays ) بطريقة الصب ( casting ) . شملت الدراسة تسجيل طيف النفوذية T ( transmittance ) في المجال ( 400 - 900 )nm، و تم حساب قيم الامتصاصية A ( Absorbance ) ، والانعكاسية R ( Reflactance ) ، ومعامل الامتصاص α (Absorption Coefficient)، ومعامل التخامد Ko ( Extiction Coefficient ) ، وقرينة الإنكسار no ( Refractive index ) لأغشية البوليستيرين قبل التشعيع وبعده . تمت دراسة تأثير أشعة على تشتت ( dispersion ) قيم قرينة الانكسار no وفقا لنموذجي ويمبل - ديدمينكو وسيللماير (Wemple - Didomenico and Sellmeier models). تبين أن أشعة تؤدي إلى زيادة النفوذية T وانخفاض قيم كل من R وA وكذلك إلى انخفاض قيم no بشكل واضح . تم حساب بعض القيم الخاصة بنموذج ويمبل - ديدمينكو مثل طاقة المهتز الأحادي Eo ( Single Oscillator energy ), وطاقة التشتت Ed ( dispersion energy ) بدلالة قرينة الانكسار no . اضافة الى ذلك تم حساب بعض القيم الخاصة بنموذج سيللماير مثل (nm) oλ ( معدل طول موجة المهتز) ( average oscillator wavelength ) ومعدل شدة طول المهتز So (average oscillator length strength ). وفقا لنموذج ويمبل - ديدمينكو فإن قيم تشتت قرينة الانكسار تتقارب من ( 1.85 ) بينما تتناقص في حالة العينة المشععة إذا تبلغ قيمتها (1.0826) عند الطاقات المنخفضة . تقترب قيم تشتت  noوفقا لنموذج سيللماير من القيمة ( 1.83 ) للعينة النقية في حين تتناقص في حالة العينة المشععة حيث تبلغ  (1.14) عند الموجات الطويلة .